A rare case of Ellis-van Creveld syndrome with primary immunodeficiency with recurrent and persistent pneumonia - Hassan, Mahmuda; Roy, Sudipta; Khan, Masuma; Mukti, Afsana; Ferdous, Zannatul; Yasmeen, B H Nazma (Northern International Medical College Journal, 2024)
Abstract not available Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 594-597